Formulasi Sediaan Tablet Ekstrak Daun Talas (Colocasia esculenta (L.) Schott.) Dengan Variasi Kadar Polivinil Pirolidon (PVP) Sebagai Bahan Pengikat - St Rahmatullah; Dwi Bagus Pambudi; Yulian Wahyu Permadi; Nurul Hikmah (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Taro leaves (Colocasia Esculenta (L.) Schott.) contain alkaloids, saponins, tannins, flavonoids and polyphenols. Utilization of taro leaves requires new innovations by developing ways of making tablets, which increase the convenience of use through more comfortable use and more stable storage compared to liquid pharmaceutical preparations or suspensions. The aim of this study was to determine the effect of the comparison of variations of Polyvinylpyrrolidone (PVP) binder on the physical properties of granules and tablets and to obtain the optimum formula. Tablets were made by wet granulation process with 1%, 3% and 5% PVP. Granules were tested for water content, flow time test, angle of repose and tapping. The resulting tablets were then tested for their physical properties. Research result; Weight uniformity with 5% PVP fulfills the physical requirement of 600 g. Size uniformity fulfills the physical requirements with a yield of 2.91 mm. Hardness with 3% PVP meets the physical requirements of 5.95 kg. Fragility meets the physical requirements of 1% PVP, namely 0.4%. The disintegration time with 1% PVP met the physical requirements, namely 7.88 minutes. The results stated that variations in the concentration of the PVP binder could be formulated into tablets and the tablet binder resistance was measured which met the requirements of the best tablet physical properties. Optimal formulation is achieved in formula III with binder containing 5% PVP.